2019
DOI: 10.1371/journal.pone.0218555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical outcomes of the Test and Treat strategy to implement Treat All in Nigeria: Results from the Nigeria Multi-Center ART Study

Abstract: In December 2016, the Nigerian Federal Ministry of Health updated its HIV guidelines to a Treat All approach, expanding antiretroviral therapy (ART) eligibility to all individuals with HIV infection, regardless of CD4+ cell count, and recommending ART be initiated within two weeks of HIV diagnosis (i.e., the Test and Treat strategy). The Test and Treat policy was first piloted in 32 local government areas (LGAs). The primary objective of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
70
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 20 publications
12
70
5
Order By: Relevance
“…On top of the change in the CD4 cut off point, test and treat was also introduced to specific sub-populations (children under 5 years, TB/HIV co-infected, HBV/HIV co-infected, the HIV-positive partner in HIV sero-discordant relationship and pregnant and breastfeeding mothers (Option B+). Similar findings were reported in previous studies, which showed that patients who started ART at a higher CD4 were at risk of attrition[8, 9]. Patients starting ART at high CD4 are less sick and have low risk perception which might affect adherence to long term therapy [55].…”
Section: Discussionsupporting
confidence: 86%
“…On top of the change in the CD4 cut off point, test and treat was also introduced to specific sub-populations (children under 5 years, TB/HIV co-infected, HBV/HIV co-infected, the HIV-positive partner in HIV sero-discordant relationship and pregnant and breastfeeding mothers (Option B+). Similar findings were reported in previous studies, which showed that patients who started ART at a higher CD4 were at risk of attrition[8, 9]. Patients starting ART at high CD4 are less sick and have low risk perception which might affect adherence to long term therapy [55].…”
Section: Discussionsupporting
confidence: 86%
“…On top of the change in the CD4 cut-off point, test and treat was also introduced to specific sub-populations (children under 5 years, TB/HIV co-infected, HBV/HIV co-infected, the HIV-positive partner in HIV sero-discordant relationship and pregnant and breastfeeding mothers (Option B+). Similar findings were reported in previous studies, which showed that patients who started ART at a higher CD4 were at risk of attrition [8,9]. Patients starting ART at high CD4 are less sick and have low risk perception which might affect adherence to long term therapy [64].…”
Section: Discussionsupporting
confidence: 86%
“…Early ART initiation as measured by shorter time duration between HIV testing and ART initiation has been shown to reduce risk of attrition [6,7]. Other studies have however shown that those who initiate ART at a higher baseline CD4 may also be prone to attrition [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria adopted in 2015 a ‘test and treat’ policy of ART initiation in all PLWH regardless of CD4, clinical stage, age or population [ 6 ]. Although additional work is needed to completely achieve this goal, efforts have been made to scale-up treatment access and the number of PLWH receiving ART almost doubled between 2015 and 2018 [ 7 ].…”
Section: Introductionmentioning
confidence: 99%